A Slope Stability Based Realm Optimization Analysis for an Open Pit Mine in Cold Region: Taking Jiguanshan Molybdenum Mine for Example. (18th July 2022) - Hu, Yongyue; Li, Changhong; Li, Juzhou; Long, Dayu; Wang, Yu
Abstract : Open pit mines have a direct impact on the production efficiency and sustainable development of the enterprise by realm optimization. In the case of changing mining technology conditions and market demand, the original design realm of the mine needs to be optimized in time for the study. Therefore, based on the slope stability analysis, this paper changes the slope angle by changing the working platform size and step and section, and forms a total of four Programs I, II, III, and IV. Geostudio software was utilized to analyze the slope stability of four scenarios and obtain the slope safety coefficients under different scenarios, and the results show that Programs I, II, and III all meet the requirements of reasonable safety coefficients. Furthermore, the geological model of the slope in C profile in Program III was constructed, and the changes of slope stress and displacement during the step-by-step excavation process were analyzed, with a maximum of stress 3.5 MPa, total displacement 12.9 cm, shear should be incremental, plastic zone change is small, and the results showed that the slope structure parameters of Program III were reasonable. The geological drilling data of Jiguanshan molybdenum mine was processed with 3DMine software, the geological database was constructed, the ore body model was established, and the mine boundary optimization study was conducted, Program III was finally determined as the optimal option. The result of the boundary optimization improves the final slope angle by 1°, which can enable the mine to extract 13.334 million tons more ore, reduce the stripping ratio to 1.07m 3 /m 3, and generate economic benefits of 116 million.